2012
DOI: 10.3892/or.2012.1946
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros inhibits proliferation and, through upregulation of Slug, increases metastatic ability of ovarian serous adenocarcinoma cells

Abstract: The transcription factor Ikaros was originally found to function as a key regulator of lymphocyte differentiation. In this study, we provide the first evidence that Ikaros is expressed at higher levels in ovarian cancer tissues compared with normal ovarian tissues and is significantly associated with high FIGO stage and low differentiation state in ovarian serous adenocarcinoma. To this end, we transfected IK1 (full length of Ikaros) into the SKOV3 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Tumor growth was observed for at least cycle and wound healing assay, functional studies demonstrated that the Twist pathway indeed affected CXCL12-mediated proliferation, migration, and invasion of glioblastoma cells. Consistent with these findings, published articles also laid stress on the regulatory functions of Twist in cell migration and invasion [24,25]. Twist indeed plays different roles in tumor development.…”
Section: Discussionsupporting
confidence: 63%
“…Tumor growth was observed for at least cycle and wound healing assay, functional studies demonstrated that the Twist pathway indeed affected CXCL12-mediated proliferation, migration, and invasion of glioblastoma cells. Consistent with these findings, published articles also laid stress on the regulatory functions of Twist in cell migration and invasion [24,25]. Twist indeed plays different roles in tumor development.…”
Section: Discussionsupporting
confidence: 63%
“…However, the role of Ikaros family members in solid tumors have not been well demonstrated in the literature. IKZF1 promotes metastatic ability through upregulating Slug and matrix metalloproteinase 2 (MMP2) in ovarian cancer 30 . Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence demonstrated that dysregulation of expression of miRNAs in gastric cancer might be thought as one of the leading factors in tumorigenesis, and miRNAs can be recommended as a predictive biomarker in the diagnosis of gastric cancer patients. Besides, Twist1 has been widely reported as a poor prognosis biomarker in diverse tumors [1719]. Thus, identification of GC-related miRNAs will make for understanding of etiology of gastric cancer, and elucidation of their biological roles can facilitate the diagnosis and prognosis of gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%